2009
DOI: 10.1103/physreva.79.033616
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-breaking and symmetry-restoring dynamics of a mixture of Bose-Einstein condensates in a double well

Abstract: We study the coherent nonlinear tunneling dynamics of a binary mixture of Bose-Einstein condensates in a double-well potential. We demonstrate the existence of a type of mode associated with the "swapping" of the two species in the two wells of the potential. In contrast to the symmetry-breaking macroscopic quantum self-trapping ͑MQST͒ solutions, the swapping modes correspond to the tunneling dynamics that preserves the symmetry of the double-well potential. As a consequence of two distinct types of broken-sym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 19 publications
6
86
0
1
Order By: Relevance
“…Using this reduced system, the authors of [20] have predicted the analogous of the macroscopic quantum self-trapping phenomenon for a single bosonic component [4]. No comparison between the reduced ODE system and the full GPE dynamics has been performed, so that the question of the validity of such prediction remains open.…”
Section: Introductionmentioning
confidence: 99%
“…Using this reduced system, the authors of [20] have predicted the analogous of the macroscopic quantum self-trapping phenomenon for a single bosonic component [4]. No comparison between the reduced ODE system and the full GPE dynamics has been performed, so that the question of the validity of such prediction remains open.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on the interplay between the boson-boson interaction and the interwell spinorbit coupling (the intrawell SO coupling is zero in first approximation) in determining the importance of the interchange of atoms between the two bosonic species on the two canonical effects: self-trapping and macroscopic tunneling phenomena. In particular, we point out that an analog of the macroscopic quantum self-trapping that one observes for the variable z k [27,30] exists for the polarization z 12 as well. During the z 12 self-trapped dynamics, on the average, one bosonic component is more populated than the other one.…”
Section: Introductionmentioning
confidence: 67%
“…Let us note, however, that the effect of the repulsion between species has been discussed thoroughly in Refs. [25][26][27][28][29][30][31][32]47], where it was found that the conventional Josephson dynamics is crucially modified by this term, even leading to measure synchronization in some limits [48]. In particular, the interspecies interaction induces the presence of additional fixed points in the problem which are related to the repulsion between components.…”
Section: Josephson Dynamics In the Spin-orbit-coupled Double Wellmentioning
confidence: 99%
See 1 more Smart Citation
“…In nonlinear systems, because additional nonlinearity always give rise to the effect of SSB, phase transition and SSB are also important issues and attract great attention. Among many kinds of nonlinear systems, double-well potential (DWP) or dual-core system is the most essential model employed to study the phase transition and SSB of the nonlinear states [2][3][4][5][6][7][8][9]. In DWP system, the important process relating to the phase transition and SSB is symmetric breaking bifurcation (SBB), which determines the process of symmetric states transiting to the asymmetric ones [10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%